THE IMPACT OF THE MUJADDIDI BRANCH OF NAQSHBANDI ON SOCIAL LIFE IN CENTRAL ASIA - Mirzaeva Feruzakhon (The Conference Hub, 2025)
The article examines the evolution of the Naqshbandi-Mujaddidi order, the significance of its doctrines in social life, the activities of Mujaddidiyya shaykhs, and their scientifically grounded educational methods.
Keywords: Sufi orders, Central Asia, naqshbandi-mujaddidi order, shaykhs, murshid, murid, education, medrese, xanaqah.